Comparative examination of the tillage systems of maize on meadow chernozem soil - Ferencsik, Sándor; Rátonyi, Tamás; Fejér, Péter; Harsányi, Endre (Acta Agraria Debreceniensis, 2014)
Maize production plays a major role in the agriculture of Hungary. Maize yields were very variable in Hungary in the last few decades. Unpredictable purchase prices, periodical overproduction, the increasing occurrence of weather extremities, the uncertain profit producing ability, the soil degradation processes (physical, chemical and biological degradation) and the high expenses are risk factors for producers. Due soil tillage, there is an opportunity to reduce these risks. Based on the experimental database of the Institute of Land Utilisation, Regional Development and Technology of the University of Debrecen, Centre for Agricultural and the KITE Plc., various cultivation systems were examined with maize (Zea mays L.) as indicator plant in Jász-Nagykun-Szolnok country in 2012 and 2013. The sample area can be found in the outskirts of Kenderes on a meadow chernozem soil. On the examined plot, strip-tillage, subsoiling and moldboard ploughing were performed, each on 4.5 ha, respectively. In general, our findings show, that strip-tillage and subsoiling can be alternative tillage systems beside moldboard ploughing on meadow chernozem soils in Hungary.